A retrospective analysis of the development of psychological skills and characteristics among National Hockey League players - Pankow, K.; Fraser, S. N.; Holt, N. L. (International Journal of Sport and Exercise Psychology, 2021)
The acquisition of psychological skills and characteristics (PSCs) is an important aspect of career development in sport. PSCs may equip athletes with resources they need to navigate career transitions. Little attention has been paid to the development of PSCs in the careers of professional ice hockey players. Therefore, the purpose of this study was to examine the development of PSCs among National Hockey League (NHL) players. Using interpretive description methodology, we conducted individual semi-structured interviews with six NHL players (4 current players, 2 retired players). Data were transcribed verbatim and subjected to a reflexive thematic analysis. Results were organised around three career stages (minor, junior, and professional hockey). In minor hockey, participants developed interpersonal (teamwork, leadership, accountability, and being a good teammate) and individual (work ethic, discipline, and commitment) psychological characteristics within a supportive social environment. During junior hockey, participants developed performance-oriented psychological characteristics (dealing with adversity, focus on the present, emotional regulation, having confidence in one`s abilities and a positive attitude) and psychological skills (reframing adversity as a challenge) arising from experiences of adversity and success. Finally, during professional hockey, they developed and refined performance-oriented psychological skills (visualisation, self-talk, reflection, and thought-stopping) while also focusing on being a good teammate to promote their career longevity. These findings indicate there was a chronological pattern in the development of PSCs among the NHL players studied. A practical implication is that building foundational psychological characteristics may facilitate the later development of performance-oriented PSCs.